Pengaruh Penggunaan Media Sosial Instagram, Word Of Mouth dan Daya Tarik Wisata Terhadap Keputusan Berkunjung Wisatawan Pada Objek Wisata Sawah KalimbuangKabupaten Toraja Utara - Esmeralda Esmeralda; Althon K. Pongtuluran; Chrismesi Pagiu (Universitas Kristen Indonesia Toraja, 2023)
The purpose of this study was to find out whether social media Instagram, word of mouth, tourist attractions influence the decision to visit the Kalimburan Rice Fields Tourism Object. Data collection process techniques from this study are: Observation and Questionnaire. The analysis technique uses multiple linear regression tests. The results of the partial test (t test) show that the social media variables Instagram, word of mouth, tourist attraction influence the decision to visit the Kalimburan Rice Field Tourism Object. Meanwhile, the results of the simultaneous test (F test) showed that the social media variable Instagram, word of mouth, tourist attraction had an effect on the decision to visit the Kalimburan Rice Fields Tourism Object.